(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about Iraq has sought to develop its natural reserves and forests to sustain natural diversity and preserve rare wild animals and plants from the danger of extinction and overview at a reserve in eastern Baghdad and tracking the living creatures protect them from extinction and promoting sustainable management of living natural resources through the adoption of practices that would integrate the needs of biodiversity conservation and development priorities.